Inovar Auto : Evaluating Brazil's Automative Industrial Policy to Meet the Challenges of Global Value Chains - Sturgeon, Timothy (World Bank, Washington, DC, 2017)
Brazil's automotive industry is unwell. Productivity and trade performance are low, consumer prices are high, local companies are bit players both at home and abroad, and innovation is almost nonexistent. The cumulative (opportunity) costs of Brazil's protectionist automotive policies, which have been in place in some form since the 1950s – while immeasurable – are certainly very high. However, it is not accurate to say that they have failed, since Brazil would probably not have an automotive industry today without them, at least not one that employs nearly 500,000 workers in the manufacturing sector. According to the most recent figures, 89 percent of vehicles sold in Brazil were produced in the country, and very recently, exports have surged to 30 percent of production. However, Brazil has a large trade deficit in automotive parts and components and finished vehicle exports are volatile, used mainly as a 'pressure relief valve' during downturns in the domestic market. Local content figures are not available, signaling a major flaw in the accountability and transparency of Brazil’s automotive industrial policy regime.